Hisonotus acuen, a new and phenotypically variable cascudinho (Siluriformes, Loricariidae, Hypoptopomatinae) from the upper rio Xingu basin, Brazil - Silva, Gabriel S. C. [UNESP]; Roxo, Fabio F. [UNESP]; Oliveira, Claudio [UNESP] (Pensoft Publ, 2014)
A new species of Hisonotus is described from the headwaters of the rio Xingu. The new species is distinguished from its congeners by having a functional V-shaped spinelet, odontodes not forming longitudinal aligned rows on the head and trunk, lower counts of the lateral and median series of abdominal plates, presence of a single rostral plate at the tip of the snout, absence of the unpaired platelets at typical adipose fin position, yellowish-tipped teeth, absence of conspicuous dark saddles and stripe on the body and higher number of teeth on the premaxillary and dentary. The new species, Hisonotus acuen, is restricted to headwaters of the rio Xingu basin, and is the first species of the genus Hisonotus described from the rio Xingu basin. Hisonotus acuen is highly variable in aspects of external body proportions, including body depth, snout length, and abdomen length. This variation is partly distributed within and among populations, and is not strongly correlated with body size. PCA of 83 adult specimens from six allopatric populations indicates the presence of continuous variation. Therefore, the available morphological data suggest that the individuals inhabiting the six localities of rio Xingu represent different populations of a single species. Low intraspecific variation in mitochondrial Cytochrome oxidase subunit I (COI) provides corroborative evidence.
Keywords: Biodiversity; Cascudinhos; Fresh-water; Neotropical fish; Taxonomy